The Hydration State of Bone Tissue Affects Contrast in Neutron Tomographic Images - Törnquist, Elin; Le Cann, Sophie; Tengattini, Alessandro; Helfen, Lukas; Kok, Joeri; Hall, Stephen A.; Isaksson, Hanna (Frontiers in Bioengineering and Biotechnology, 2022)
Neutron tomography has emerged as a promising imaging technique for specific applications in bone research. Neutrons have a strong interaction with hydrogen, which is abundant in biological tissues, and they can penetrate through dense materials such as metallic implants. However, in addition to long imaging times, two factors have led to challenges in running in-situ mechanical characterization experiments on bone tissue using neutron tomography: (i) the high water content in specimens reduces the visibility of internal trabecular structures; (ii) the mechanical properties of bone are dependent on the hydration state of the tissue, with drying being reported to cause increased stiffness and brittleness. This study investigates the possibility of improving image quality in terms of neutron transmission and contrast between material phases by drying and rehydrating in heavy water. Rat tibiae and trabecular bovine bone plugs were imaged with neutron tomography at different hydration states and mechanical testing of the bone plugs was carried out to assess effects of drying and rehydration on the mechanical properties of bone. From analysis of image histograms, it was found that drying reduced the contrast between bone and soft tissue, but the contrast was restored with rehydration. Contrast-to-noise ratios and line profiles revealed that the contrast between bone tissue and background was reduced with increasing rehydration duration but remained sufficient for identifying internal structures as long as no free liquid was present inside the specimen. The mechanical analysis indicated that the proposed fluid exchange protocol had no adverse effects on the mechanical properties.